2022
DOI: 10.1186/s40359-022-00855-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental bonding, social isolation and loneliness: do associations persist in later life and is isolation a mediator between parental bonding and loneliness?

Abstract: Background Poor parental bonding in childhood has been associated with loneliness in younger populations. Whether these associations persists into middle and older adulthood is unclear. Additionally, given the overlapping relationship between loneliness and social isolation we sought to explore the role of social isolation in any associations present i.e. are those reporting worse parental bonding lonely due to less connections or are they more likely to be lonely regardless of isolation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…Moreover, in accordance with several similar studies that have confirmed the associations between adverse childhood experiences and psychological wellbeing among young or older adults (Burns et al, 2022; Vederhus et al, 2022), the current results show that childhood bullying victimization significantly increases the possibility for middle and older adults to be trapped in social isolation, further improving their levels of depression. Specifically, exposure to childhood bullying victimization blocks the initial reserve of individuals’ interpersonal abilities at the early stage (Barile et al, 2015), causing them unable to obtain sufficient and high-quality social relationships to maintain mental health in the future (Uchino et al, 1996), and also damages their stress response regulation systems (Subramaniam et al, 2020), further forming stable negative coping strategies of avoidance and withdrawal (Bjereld, 2018), which is unfavorable for them to get out of the state of social isolation (Nicholson, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in accordance with several similar studies that have confirmed the associations between adverse childhood experiences and psychological wellbeing among young or older adults (Burns et al, 2022; Vederhus et al, 2022), the current results show that childhood bullying victimization significantly increases the possibility for middle and older adults to be trapped in social isolation, further improving their levels of depression. Specifically, exposure to childhood bullying victimization blocks the initial reserve of individuals’ interpersonal abilities at the early stage (Barile et al, 2015), causing them unable to obtain sufficient and high-quality social relationships to maintain mental health in the future (Uchino et al, 1996), and also damages their stress response regulation systems (Subramaniam et al, 2020), further forming stable negative coping strategies of avoidance and withdrawal (Bjereld, 2018), which is unfavorable for them to get out of the state of social isolation (Nicholson, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In the Chinese context, this issue is particularly pronounced due to the widespread phenomenon of “empty-nest elderly” resulting from rapid societal changes (Tang et al, 2021), which refers to the social phenomenon wherein adult children or grandchildren migrate from rural to urban areas or from the Midwest to the East of China for work or education, leaving their elderly parents or grandparents living alone. While previous research has predominantly focused on the association between functional health (e.g., cognitive function and physical function) on middle and older adults’ social isolation (Luo et al, 2021), emerging evidence suggests that childhood bullying victimization may also play a role in predicting social isolation in later life (Burns et al, 2022; Vederhus et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While bereavement or loss is understudied in relation to loneliness in younger people, quantitative studies have noted associations between loneliness and parental bonding in adolescents, university students, and young adults up to the age of 31 [43][44][45] and even among older adults aged 50 and over [46], which supports the identification of this theme in the current study in relation to those who were chronically lonely throughout life (group one). We noted, however, that the absence of a parent alone was not universally predictive of chronic loneliness.…”
Section: Themes Identified In Relation To the Literature On Lonelinesssupporting
confidence: 84%
“…In the psychological literature, parental overprotection has been mainly linked to anxiety disorders (e.g., Van der Bruggen et al, 2008 ), but it is obvious how overprotection could also be involved in ESW, as this type of parenting is likely to promote dependency and hinder the young person to function separately from his/her parents. Interestingly, there is some support for the notion that overprotection is associated with social isolation and loneliness, which can be regarded as proxies of ESW (Burns et al, 2022 ).…”
Section: Origins Of Eswmentioning
confidence: 99%